2020
DOI: 10.1186/s13071-020-04422-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site diagnosis of canine giardiosis: time versus performance

Abstract: Background Infections by protozoans of the genus Giardia are a common cause of diarrhea in dogs. Canine giardiosis constitutes a disease with a zoonotic potential; however, it is often underestimated due to its challenging diagnosis. The objective of the study was to assess the diagnostic performance of an immunochromatographic strip test (SpeedTMGiardia, Virbac, France) comparing it with microscopy (zinc sulfate flotation) by utilizing the combination of an enzyme immunoassay (ProSpecTTMGiardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…And it turned out that the parasite diagnosed with this technique and study is close to the type of Giardia lamblia, which is the most common and found in dogs. The results of the current study are in agreement with the findings of ( (Symeonidou et al,2020) They confirmed that the results of the microscopic examination and the rapid test gave a sensitivity rate of 58.6% and 86.2, respectively, and a specificity of 100%. The reason for the difference may be due to the intermittent shedding of cysts from infected dogs ranging from one to three days, so the examination of samples must be repeated at least three times.…”
Section: Positive Samples For Microscopy Positive Samples For Indirec...supporting
confidence: 92%
See 1 more Smart Citation
“…And it turned out that the parasite diagnosed with this technique and study is close to the type of Giardia lamblia, which is the most common and found in dogs. The results of the current study are in agreement with the findings of ( (Symeonidou et al,2020) They confirmed that the results of the microscopic examination and the rapid test gave a sensitivity rate of 58.6% and 86.2, respectively, and a specificity of 100%. The reason for the difference may be due to the intermittent shedding of cysts from infected dogs ranging from one to three days, so the examination of samples must be repeated at least three times.…”
Section: Positive Samples For Microscopy Positive Samples For Indirec...supporting
confidence: 92%
“…It was found through the current results that the rapid immune test technique (Rapid test) recorded a diagnosis rate of the Giardia parasite amounted to 14.2%. The results of the current study agreed with what was reported by (Alharbi et al,2020;Symeonidou et al,2020) They confirmed that the rapid test technique is easy to perform to detect Giardia infection and increases the efficiency of laboratory diagnostic techniques in addition to reducing time. The results of the current study to determine the sensitivity and specificity of the rapid test and microscopic examination of dogs infected with Giardia parasite showed a sensitivity rate of 19% and a specificity of 100%.…”
supporting
confidence: 93%
“…was more frequently found in cats with diarrheic feces [6,43,44]. The rate of infection with G. duodenalis in cats is likely to be underestimated in this study, as the use of the flotation method has less sensitivity and a bigger probability of false-negative results in comparison with the more recommended assays such as PCR, ELISA, and immunochromatographic tests [45]. Therefore, an accurate frequency of feline giardiosis should be assessed, especially in diarrheic cats.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the identification of the lack of a main building on the farm as the only significant predictor for the presence of Giardia cysts in samples from goats ( Table 5 ) could not be associated with a plausible explanation of clinical significance. In any case, the difficulties associated with an accurate Giardia diagnosis, arising from the intermittent excretion of the parasite [ 36 , 37 ], present challenges for the accurate detection of infection status.…”
Section: Discussionmentioning
confidence: 99%